YANG MINORITAS : YANG TERTINDAS (ANALISIS KONFLIK AHMADIYAH VS "ISLAM") - Sujadmi Sujadmi (Society, 2013)
Power is everywhere, so is revealed by Foucault. Power possessed by the majority who don’t rarely brought the existence of a conflict with minority parties. Similarly, religion, religions are like two sides of a coin. On the one hand the belief gave way towards peace, but on the other side of religion considered to be a source of division in the community. The religion of the majority religion is considered as a powerful or have power in society even more dominant than countries with other religions are minorities. Religious conflicts have often occurred in different countries and even Indonesia are in fact as a multicultural country in religion. Conflict not only between different faiths, even some internal conflict / co-religionists because of differences in the interpretation of scripture that ultimately led to anarchy. Religious issues will be difficult to overcome if both parties use their eyes in search of the truth. As a multicultural country, should all parties can appreciate and respect each other and understand and understand the Human Rights owned by each indivvidu. Freedom of religion is one of the rights that should be protected. In the cases of minorities in this country, should the state government in this case is able to protect its citizens and uphold human rights in the embrace and believe in a religion.